Identification of a new stripe rust resistance gene in Chinese winter wheat Zhongmai 175 - Jia-ling LU; Can CHEN; Peng LIU; Zhong-hu HE; Xian-chun XIA (Journal of Integrative Agriculture, 2016)
Stripe rust is a serious foliar disease posing a grave threat to wheat production worldwide. The most economical and environmentally friendly way to control this disease is to breed and deploy resistant cultivars. Zhongmai 175 is an elite winter wheat cultivar conferring resistance to a broad spectrum of Puccinia striiformis f. sp. tritici (Pst) races. To identify the resistance gene in the cultivar, genetic analysis was conducted using the parents, F1, F2 and F2:3 populations derived from the cross of Lunxuan 987/Zhongmai 175. Segregations in the F2 and F2:3 populations indicated a single dominant gene conferring resistance to stripe rust in Zhongmai 175, temporarily designated YrZM175. Bulked segregant analysis (BSA) with wheat iSelect 90K SNP array determined a preliminary location of YrZM175. Subsequently, YrZM175 was mapped on chromosome 2AS using simple sequence repeats (SSR), expressed sequence tags (EST) and newly-developed kompetitive allele specific PCR (KASP) markers, being flanked by Xgwm636 and Xwmc382 at genetic distances of 4.9 and 8.1 cM, respectively. Comparison of reaction patterns of YrZM175 on 23 Pst races or isolates and pedigree analysis with other genes on chromosome 2AS suggested that it is likely to be a new gene for resistance to stripe rust. The resistance gene and linked molecular markers will be useful in wheat breeding targeting for the improvement of stripe rust resistance.